Media Coverage of Taliban: Is Peace Journalism the Solution?. (June 2016) - Hussain, Shabir
This article combines quantitative and qualitative analysis to investigate the reporting of the Taliban conflict in Pakistan media and finds the coverage escalatory and elitist from the peace journalism perspective. While the security-related aspects of the conflict are highlighted, the problems of victims are ignored. The data for this study were collected through content analysis, discourse analysis and interviews with conflict reporters and analysts. The key findings of this study are quite consistent with the existing peace journalism scholarship that in conflict where national interests are involved, media become nationalistic and patriotic, leaving behind the considerations of quality and good journalism.